Hutan Nagari Simancuang: Pengelolaan Hutan Skema Perhutanan Sosial di Kabupaten Solok Selatan - Rahman, Fajri; Irwandi, Ade; Apriwan, Apriwan (Universitas Batanghari Jambi, 2024)
The aim of this research is to describe and explain social forestry scheme forest management in Jorong Simancuang, South Solok Regency, West Sumatra Province. The research method uses a descriptive approach with data collection through interviews. The Infoman consists of the Nagari Forest Management Institute (LPHN), the Social Forestry Business Group (KUPS), community leaders, companions of the Indonesian Conservation Group (KKI) Warsi and the Farmers' Group. The results of this research show that social forestry is present in the Jorong Simancuang Village community, strengthening the legitimacy of the community's desire to protect their forests as a source of water for agriculture and forests as a source of farming economy.